Subjective perception of time as a temporal fictional image - Gaukhar I. Issina, Ella V. Nesterik,; Darina Y. Amanbekova, Fazira A. Kakzhanova (Opción, 2019)
The article is concerned with subjective perception of time, alsoknown as psychological time, in the capacity of a textual category anda fictional image via comparative qualitative research methods. As thebasis for this hypothesis in its turn we refer to the results of similarinvestigations in literary studies, psychology and text linguistics. As aresult, words describing real fictional time and space quite oftenappear in descriptions of psychological time. In conclusion, thecategory of fictional time plays a very important role in the modelingof the subjective perception of time by characters.